Additions to Termitomyces aurantiacus growing termite comb-associated fungi - Yang, Erfu; Karunarathna, Samantha C.; Shao, Shicheng; Han, Lisu; Samarakoon, Milan C.; Elgorban, Abdallah M.; Chiu, Chuni; Tibpromma, Saowaluck; Promputtha, Itthayakorn (Phytotaxa, 2025)
The Macrotermitinae termites, the only lineage that maintains and cultivates Termitomyces species as nutritional ectosymbionts, resemble human agricultural activities. Found in savannah and rainforest ecosystems across Africa and Asia, these termites enhance the physical and chemical properties of soil and influence the composition of microbial communities. However, fungus-growing termites also pose significant threats to agriculture and forestry. Termitomyces species, dominant fungi propagated within biomass-containing cork-like structures (“fungus comb”), also contain trace amounts of non-termitomyces fungi. In the summer of 2022, we collected combs of the subterranean fungus-growing termites that cultivate Termitomyces aurantiacus from the Xishuangbanna Tropical Botanical Garden. To validate our results, we used a culture-dependent method to isolate fungi residing in termite fungus gardens. This method was further validated by confirming their taxonomic classification through morphological and phylogenetic results. The findings of these studies led to the identification of one new (Geotrichum xishuangbannaensis) and four known (Paecilomyces formosus, Paecilomyces lagunculariae, Pleurostoma richardsiae, and Pseudallescheria angusta) species. We provide comprehensive descriptions, photographic illustrations of morphological characteristics, and phylogenetic trees of the taxa.